The Effect of Triplet Production on Pair / Compton Cascades in Thermal Radiation - Mastichiadis, A.; Protheroe, R. J.; Szabo, A. P. (1994)
We calculate the spectrum of photons resulting from electromagnetic cascades through thermal radiation, and examine the consequences of including triplet production in these cascades. We assume that the cascade is one-dimensional, and we find that this approximation is justified in the present work for thermal radiation with temperature less than 10-3 mc2. Results are obtained for both monoenergetic and power-law primary spectra, and for a variety of path lengths. We find that triplet production is particularly important in electron-photon cascades through thermal radiation when the primary energy exceeds 105m2c4/kT for propagation over small path lengths. The importance of triplet production decreases as the path length increases, and it has no effect on saturated cascades.
Keywords: Astrophysics; radiation mechanisms: non-thermal - radiative transfer - gamma-rays: theory